2007
DOI: 10.1111/j.1365-2494.2007.00569.x
|View full text |Cite
|
Sign up to set email alerts
|

Liveweight gains of lambs from Caucasian clover/ryegrass and white clover/ryegrass swards on soils of high and low fertility

Abstract: Summary The high nutritive value and persistence under a wide range of climatic and soil fertility conditions make Caucasian clover a potentially useful forage legume but there is little information about the performance of livestock grazing Caucasian clover/grass swards. This study compared liveweight gains of lambs grazing Caucasian clover/perennial ryegrass and white clover/perennial ryegrass swards on high fertility (Olsen P 20 mg L−1, SO4‐S 12 mg kg−1) and low fertility (Olsen P 11 mg L−1, SO4‐S 7 mg kg−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…, 2008). In Canterbury, New Zealand, soil Olsen P (11 and 20 mg/L) had no effect on individual lamb LWG and clover content of irrigated swards, but increased P contents in ryegrass (0.36–0.45%) and clover (0.34–0.36%) herbage and LWG in kg/ha/yr over 3 yrs (Black et al. , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…, 2008). In Canterbury, New Zealand, soil Olsen P (11 and 20 mg/L) had no effect on individual lamb LWG and clover content of irrigated swards, but increased P contents in ryegrass (0.36–0.45%) and clover (0.34–0.36%) herbage and LWG in kg/ha/yr over 3 yrs (Black et al. , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of Caucasian clover (Trifolium ambiguum; CC) over traditional legumes has been illustrated in a number of animal and pasture production studies (Taylor & Smith 1998). For example, at an irrigated lowland site in Canterbury, Black et al (2007) reported greater liveweight gain for lambs grazing mixed CC-ryegrass (Lolium perenne; RG) pastures than white clover (T. repens; WC)-RG pastures. Similarly, in Wisconsin, USA, Mouriño et al (2003) showed that the liveweight gain of steers on CC-grass pastures was 20% greater than on red clover (T. pratense)-grass pastures.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies (e.g. Black et al ., 2007) have reported higher sheep liveweight gains and higher CP concentrations in herbage of Caucasian clover than in white clover‐based swards.…”
Section: Discussionmentioning
confidence: 86%